(untitled) (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2025)
This research aims to examine and analyze the effectiveness of deposits in increasing the effectiveness of reporting PPh Article 23. The method used in this research is a quantitative descriptive method. The population in this study is all taxes deposited and reported by the TPI Bandung Class I Immigration Office for the 2022-2023 period. The sample in this research is all article 23 income tax deposited and reported by the TPI Bandung Class I Immigration Office for the 2022-2023 period. The sampling process uses a purposive sampling method. The data used is Secondary Data. The data analysis technique used is multiple linear regression on IBM SPSS Statistics version 20 software. The results of the research show that the deposit effectiveness variable has a positive and significant effect on reporting effectiveness